1998
DOI: 10.1002/(sici)1099-1646(199807/08)14:4<341::aid-rrr504>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance by aquatic plant management in streams: Effects on benthic invertebrates

Abstract: The effect of aquatic plant removal on benthic invertebrates and their habitat was studied in two macrophyte‐rich streams of the Swiss Plateau. In each stream, habitat conditions (macrophyte biomass, current velocity, water depth) and invertebrate densities were monitored in a control reach and in a reach where plants were removed by cutting. Biological samples were taken and physical parameters measured on three dates before and six dates after plant removal in both reaches. Responses to plant removal were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 36 publications
3
28
0
1
Order By: Relevance
“…and Parachironomus arcuatus, Chironomidae) (Dukowska et al 1999(Dukowska et al , 2005. On the other hand, macrophytes may create favorable conditions for pelophilous zoobenthos, such as Oligochaeta and large-sized Chironomini (Chironomidae), by trapping fine particulate organic matter on the bottom (Cogerino et al 1995, Kaenel et al 1998, Grzybkowska et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…and Parachironomus arcuatus, Chironomidae) (Dukowska et al 1999(Dukowska et al , 2005. On the other hand, macrophytes may create favorable conditions for pelophilous zoobenthos, such as Oligochaeta and large-sized Chironomini (Chironomidae), by trapping fine particulate organic matter on the bottom (Cogerino et al 1995, Kaenel et al 1998, Grzybkowska et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have investigated the spatial distribution of invertebrates within macrophytes (e.g. Tokeshi and Pinder 1985;Pinder 1992), and within the surrounding channel bed (Armitage 1995;Kaenel et al 1998). They have suggested that invertebrate taxa recorded in specific areas of plant stands may reflect their hydraulic requirements (Tokeshi and Pinder 1985;Gunn 1985;Pinder 1992;O'Hare and Murphy 1999) either directly in terms of tolerance to mean flows and turbulence intensity or indirectly through oxygen and food availability.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophytes also may create favorable conditions for pelophilous zoobenthos by trapping FPOM (Armitage 1984, Cogerino et al 1995, Pardo and Armitage 1997, Kaenel et al 1998, Gnybkowska et al 2003. In the Drzewiczka River, rnacrophyte cover was the dominant habitat during DI and was characterized by a high abundance of simuliids, orthoclads, and ephemeropterans associated with Potamogeton spp.…”
Section: Poolmentioning
confidence: 99%